Implementation of Retention and Turnover Practices for Migrant Filipino Teachers in Bangkok, Thailand: Basis for an Action Plan - MAEd, Antonette Macabasag Epanto LPT (Asian Journal of Multidisciplinary Studies, 2024)
The study investigated the retention and turnover practices of migrant Filipino teachers in Bangkok, Thailand. The study employed purposive sampling, targeting primary, secondary, and tertiary institutions employing Filipino teachers. Sixty-three school heads participated, providing insights into school profiles and the challenges faced by these educators. To explore this problem, a pre-survey was conducted to identify relevant variables, including school profile turnover and retention practices. Statistical analyses, such as frequency counts, percentages, and mean scales, summarized the data, while Spearman and Point Biserial correlations examined relationships between school profiles and retention strategies. Findings indicated the current state of retention and turnover practices among migrant Filipino teachers, highlighting areas for improvement and the need for tailored strategies. Recommendations include enhancing formal recognition programs, strengthening work-life balance initiatives, and refining turnover practices to create supportive environments. The implications extended beyond academia, providing practical insights for policymakers, school administrators, and educators. By implementing these strategies, schools can better meet the needs of migrant teachers, fostering higher retention rates and improving educational quality in Bangkok. This research emphasizes the importance of proactive measures to address migrant teachers' needs and promote inclusive educational practices.